Integrating Indoor Hibernation into the Italian Outdoor Snail Farming System: A Potential Solution for Colder Climates - Ramona Ștef; Dan Manea; Anișoara Aurelia Ienciu; Emilian Onișan; Dragoș Vasile Nica; Alin Cărăbeț (Animals)
(1) Background: Hibernation in Lutrasil-covered enclosures led to elevated mortality rates for Cornu aspersum on Romanian farms. This two-year study evaluated the feasibility of adapting indoor hibernation technology to the Italian outdoor snail farming (IOSF) system as a solution for overwintering mature C. aspersum snails. (2) Methods: Body weight, survival rates, and mortality factors during key hibernation phases (purging and overwintering) were monitored in three commercial snail farms using different hibernation scenarios. Labor efficiency was evaluated, comparing the use of micro shelters vs. hand-picking for snail collection. We analyzed post-purging/post-hibernation weight loss and mortality in hibernation spaces with and without proper thermal insulation. Mortality causes were also investigated. (3) Results: Using micro shelters significantly reduced labor time for snail collection. Weight loss during purging, but not during overwintering, were similar between groups. Post-hibernation survival ranged from 69% to 79% for comparable hibernation durations. Significantly lower survival was associated with significantly higher weight loss and using hibernation spaces with minimal thermal insulation. Predators exerted a very limited effect on post-hibernation survival, with most death appearing to be related to environmental causes. (4) Integrating indoor hibernation into the IOSF system is a promising strategy for the successful rearing of C. aspersum in colder climates.